Nursing strategies to reduce the risk of therapeutic obstinacy in artificial nutrition - Afonso, Tânia dos Santos (2021)
Background: Nurses have an important role in maintaining a patient's nutrition near the end of life. Aims: To define nursing nutrition strategies with the person near the end of life and their families; systematise the elements to be considered in artificial nutrition decision-making and evaluate the nursing interventions' influence on therapeutic obstinacy risk. Methods: A sample of 11 articles were selected and the results considered strategies to promote oral feeding before artificial nutrition; the follow-up of the health-disease process by nurses and described the nurse's role as a privileged patient advocate in the defence of the ethical principles of decision-making. These principles consider symptomatology, prognosis, psychology and the emotional significance of nutrition. Conclusion: Nurses are qualified professionals with a critical role in the patient's care due to the proximity they have with the patient; the evidence seems to show a relationship between nursing interventions and the reduction of the risk of therapeutic obstinacy; however, there are no studies in this specific area.